2006
DOI: 10.1080/08916930600739456
|View full text |Cite
|
Sign up to set email alerts
|

Complement in lung disease

Abstract: Complement proteins play an integral role in both innate and adaptive immune responses of the host. Complement activation leads to the formation of bioactive molecules including the anaphylatoxins, C3a and C5a, and the lytic membrane attack complex (C5b-9). These molecules trigger a series of events that culminate in the recruitment of phagocytic cells, release of cytokines/chemokines and reactive oxygen species, enhanced expression of adhesion molecules and apoptosis at the site of inflammation. Several anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 56 publications
1
45
0
Order By: Relevance
“…Complement cascade is also activated in the three time points of our model. Previous authors have shown that C3 and C5 play a role in asthma pathogenesis, and our observation of a continuous upregulation of complement cascade pathway (C3 and C1q genes) further validates the idea that complement could be a suitable therapeutic target (12,32). Furthermore, an upregulation of all subunits of C1q complex (C1qa, C1qb, and C1qc) was observed in our model throughout the allergen exposure, suggesting that a therapeutic intervention could take place at an earlier stage of the complement cascade, targeting C1q.…”
Section: Discussionsupporting
confidence: 54%
“…Complement cascade is also activated in the three time points of our model. Previous authors have shown that C3 and C5 play a role in asthma pathogenesis, and our observation of a continuous upregulation of complement cascade pathway (C3 and C1q genes) further validates the idea that complement could be a suitable therapeutic target (12,32). Furthermore, an upregulation of all subunits of C1q complex (C1qa, C1qb, and C1qc) was observed in our model throughout the allergen exposure, suggesting that a therapeutic intervention could take place at an earlier stage of the complement cascade, targeting C1q.…”
Section: Discussionsupporting
confidence: 54%
“…In case of pneumococcal infections, the activation of the classical pathway has been suggested to be a major host-defense mechanism (34). Moreover, classical pathway activities have been detected in the lung and the airway epithelium (35,36). Apart from the naturally occurring Abs, acute-phase proteins such as CRP and serum amyloid P component protein that bind both S. pneumoniae and C1q have been suggested to play a role in complement-mediated immunity against this pathogen (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of marked complement activation, it seems likely that the generation of C3a and C5a, each with significant chemotactic activities, contributed to this inflammation. Complement activation products are capable of inducing chemokine release (64,65), and tubular cells can be a major source of chemokine production in vivo (66) and in vitro (66,67). Although the renal pathologic features in Crry-deficient mice have dissimilarities from HUS, it is notable that marked upregulation of CXC and CC chemokines has been observed in human and experimental HUS (31,32), including CXCL1, 5, 9, and 10 and CCL2 and 5, as we observed here.…”
Section: Discussionmentioning
confidence: 99%